Stock market reaction to U.S. tariff announcements: Evidence from ASEAN - Alvin Rezki Kurniawan; Titi Dewi Warninda; Murdiyah Hayati (Priviet Social Sciences Journal, 2026)
This study examines the impact of United States reciprocal tariff announcements on stock market reactions in ASEAN countries using six major indices: IHSG (Indonesia), STI (Singapore), FTSE KLCI (Malaysia), SET (Thailand), PSEi (Philippines), and VN Index (Vietnam) in 2025. Three events are analyzed: the initial tariff announcement on April 2, 2025, the tariff pause announcement on April 9, 2025, and the tariff adjustment announcement on August 1, 2025. An event study method is applied with a 120-day estimation period and an event window from t0 to t+3 using the mean-adjusted model. Hypothesis testing employs the one-sample t-test or the Wilcoxon signed-rank test based on data normality. The results show that the initial tariff announcement generated significant negative cumulative abnormal returns, particularly in Vietnam and Singapore. The tariff pause announcement produced significant positive abnormal returns, indicating a market rebound following reduced policy uncertainty. The tariff adjustment announcement resulted in more moderate reactions, with insignificant daily abnormal returns but a positive cumulative effect. Overall, ASEAN stock markets react to U.S. tariff announcements, although price adjustment is not always immediate, indicating deviations from full semistrong market efficiency.